Towards an understanding of older adult educational tourism through the development of a three-phase integrated framework. Issue 2 (28th January 2016) - Sie, Lintje; Patterson, Ian; Pegg, Shane
Abstract : As a direct consequence of global ageing patterns, older travellers have become a significant proportion of annual total holiday spending. In addition, this has also brought with it a shift in the types of travel experiences that older travellers are now choosing. Educational and cultural touristic experiences are now becoming popular options for many older individuals, as they provide greater opportunities for meaningful engagement as well as tapping into their renewed interest for history and nostalgia. At the same time, older travellers are placing a greater value on lifelong learning that may help to enrich their life. This paper provides a comprehensive review of the educational travel experiences of older adults through the development of an integrated framework that links the three stages of educational travel: pre-travel, participation, and post-travel. It is envisaged that this framework will contribute to the development of a conceptual model for successful ageing that acknowledges the significant impact that educational travel experiences will have on the well-being of older tourists.